James Rudolph Garfield papers - Garfield, James Rudolph, 1865-1950.; Garfield, Helen Newell, 1866-1930.; Garfield, James A. (James Abram), 1831-1881.; Garfield, Lucretia Rudolph, 1832-1918.
Correspondence, diaries (1880-1948), professional and official records, speeches, legal case files, articles, scrapbooks, memorabilia, and other papers relating to Garfield's activities as a lawyer, member of the Ohio senate, U.S. civil service commissioner, commissioner at the Bureau of Corporations in the U.S. Dept. of Commerce and Labor, and U.S. secretary of the interior, and to municipal and cultural affairs in Cleveland and Mentor, Ohio. Organizations represented include the Academy of Political Science, National Conservation Association, Progressive and Republican parties, and Roosevelt Memorial Association. Includes correspondence and other material relating to his father, James A. Garfield; extensive correspondence with his mother, Lucretia Rudolph Garfield; and correspondence of his wife, Helen Newell Garfield. Correspondents include Newton Diehl Baker, Viscount James Bryce, Calvin Coolidge, Warren G. Harding, Frederic Clemson Howe, Gaillard Hunt, J. J. Jusserand, Gifford Pinchot, Edith Kermit Carow Roosevelt, Theodore Roosevelt, L. S. Rowe, Woodrow Wilson, and Leonard Wood.
U.S. secretary of the interior, Ohio state senator, conservationist, lawyer, and son of President James A. Garfield.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Garfield, James A. -- 1831-1881 -- Family; Harding, Warren G. -- 1865-1923 -- Correspondence; Howe, Frederic C., -- 1867-1940 -- Correspondence; Hunt, Gaillard, -- 1862-1924 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Roosevelt, Edith Kermit Carow, -- 1861-1948 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Rowe, L. S. -- 1871-1946 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Academy of Political Science (U.S.); National Conservation Association (U.S.); Ohio. -- General Assembly. -- Senate; Progressive Party (1912); Republican Party (U.S. : 1854- ); Roosevelt Memorial Association; United States. -- Bureau of Corporations; United States. -- Department of Commerce and Labor; United States. -- Department of the Interior; United States Civil Service Commission; Cleveland (Ohio) -- Social life and customs; Mentor (Ohio) -- Social life and customs; Ohio -- Politics and government; United States -- Politics and government; Cabinet officers; Conservationists; Lawyers